2021
DOI: 10.1055/s-0041-1729856
|View full text |Cite
|
Sign up to set email alerts
|

Is Lupus Anticoagulant a Significant Feature of COVID-19? A Critical Appraisal of the Literature

Abstract: The term “lupus anticoagulant (LA)” identifies a form of antiphospholipid antibodies (aPLs) causing prolongation of clotting tests in a phospholipid concentration-dependent manner. LA is one of the laboratory criteria identified in patients with antiphospholipid (antibody) syndrome (APS). The presence of LA in patients with APS represents a significant risk factor for both thrombosis and pregnancy morbidity. There have been several reports of similarities between some of the pathophysiological features of COVI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 79 publications
1
46
0
Order By: Relevance
“…[73][74][75] A role for lupus anticoagulant and antiphospholipid antibodies has been suggested for pathogenesis of COVID-19-associated coagulopathy. 52,[76][77][78][79][80] In severely infected patients, immobility under conditions of quarantine or hospitalization is another predisposing factor of thrombosis. 81,82 Modification of the equilibrium between clot formation and degradation in favor of hypercoagulability and hypofibrinolysis, impaired endothelial function, platelet hyperactivation, and excessive immune response are emerging as major contributors to the thrombotic complications.…”
Section: Pathophysiology Of Covid-19-associated Coagulopathymentioning
confidence: 99%
“…[73][74][75] A role for lupus anticoagulant and antiphospholipid antibodies has been suggested for pathogenesis of COVID-19-associated coagulopathy. 52,[76][77][78][79][80] In severely infected patients, immobility under conditions of quarantine or hospitalization is another predisposing factor of thrombosis. 81,82 Modification of the equilibrium between clot formation and degradation in favor of hypercoagulability and hypofibrinolysis, impaired endothelial function, platelet hyperactivation, and excessive immune response are emerging as major contributors to the thrombotic complications.…”
Section: Pathophysiology Of Covid-19-associated Coagulopathymentioning
confidence: 99%
“… 73 This finding is significant in the light of COVID-19 as formation of antiphospholipid antibodies, like anti-β2 glycoprotein IgG antibodies, are associated with thrombosis in patients with COVID-19. 74 A cohort studied from France has demonstrated that a large percent of severe COVID-19 patients exhibits a detectable lupus anticoagulant. 75 However, it still remains to be established whether the presence of antiphospholipid antibodies in SARS- CoV-2 patients plays a role in infection-associated thrombosis or represents merely an association.…”
Section: Molecular Mechanism Resulting In Cic Mediated Thrombosismentioning
confidence: 99%
“…The obvious conclusion, which has been reached previously in studies of other autoimmune diseases, is that molecular mimicry may be necessary to induce auto-reactive B and T cells but is clearly not sufficient to induce autoimmune disease. [22,[83][84][85][86] This point is essential for understanding how many hospitalized COVID-19 patients are found transiently to express anti-phospholipid antibodies (aPL), anti-PL4, b2GPI, and other blood cell antibodies [7,[21][22][23][24][25][26][27]87,88] but only a fraction of these develop coagulopathies [25,30,87,88] and also why SARS-…”
Section: Interpreting the Results In Terms Of Different Autoimmune Disease Theoriesmentioning
confidence: 99%
“…The obvious conclusion, which has been reached previously in studies of other autoimmune diseases, is that molecular mimicry may be necessary to induce auto‐reactive B and T cells but is clearly not sufficient to induce autoimmune disease . [ 22 , 83 , 84 , 85 , 86 ] This point is essential for understanding how many hospitalized COVID‐19 patients are found transiently to express anti‐phospholipid antibodies (aPL), anti‐PL4, b2GPI, and other blood cell antibodies [ 7 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 87 , 88 ] but only a fraction of these develop coagulopathies [ 25 , 30 , 87 , 88 ] and also why SARS‐CoV‐2 vaccines (to be discussed in “Implications of bacterial and viral coinfections for understanding vaccine‐induced coagulopathies”) often induce autoantibodies but rarely autoimmune disease. Mimicry may frequently induce autoantibody production but rarely leads to overt autoimmune disease or, alternatively, mimics may be perceived by the immune system as “self” antigens resulting in T cell tolerance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation